THE PRIMARY CARE INFORMATION SYSTEM: POTENCIAL AND UNDER-USE IN THE DECISION-MAKING PROCESS - Ricardo Bezerra Cavalcante; Mariana Ferreira Vaz Gontijo Bernardes; Tarcísio Laerte Gontijo; Eliete Albano de Azevedo Guimarães; Valéria da Conceição Oliveira (Universidade Federal do Paraná, 2013)
This case study, with a qualitative approach, aimed to analyze how the health professionals and managers have used the Primary Care Information System in the decision-making process. Between January and July 2011, based on a semi-structured script, interviews were held with 11 professionals who use this in the ambit of the Municipal Health Department and the Regional Health Office, of the Unified Health System. The thematic mode of content analysis was used for organization and analysis of the data. It was ascertained that the Information System has potential, but that it is under-used for the decision-making process given the nature of the work process and the model of assistance, as it does not respond to the diversity of the assistential models and because of the professionals' lack of qualification. It is concluded that it is necessary to rethink the informational flow of the Information System, with a view to its use in the local decision-making process and in implanting the management of information as an institutionalized practice.